The Kind of Face You Would Expect in an Anarchist. Orwell and Anarchism (Altre Modernità, 2024)
This paper takes its cue from the study of Orwell’s political thought within the broader philological investigation necessary to translate his literary works while accounting for the complexity of their political subtext. Such exploration easily turned into an attempt to preserve the consistency of his challenging political views and accordingly recover his socio-political analyses from the banalisation these have suffered in the past few decades. Main obstacles to the critical appraisal of such analyses were the author’s inner struggle between social inhibition and polemic stance as well as his nervous tension between materialism, empiricism and aversion to abstract theorizations on the one hand and the inclination to question and debunk any perceived normality on the other hand. One of the aspects of Orwell’s intellectual contribution that proved remarkably disturbing and was consequently removed from any critical discourse on it is his intimate and troubled relationship with anarchists and anarchism. Fuelled by mutual pragmatism, such relation was strengthened by his joining the Spanish antifascist front and the subsequent, common struggles against totalitarianism and the totalitarian tendencies also within western democracies. The essay eventually focuses on the most persistent value in Orwell’s writing, “decency”, by which he meant the human-centred capacity to resist the freedom-destroying efficiency of capitalist modernity.
Keywords: George Orwell; anarchism; totalitarism; decency; resistance; anti-fascism